Challenging Conventions (De Gruyter, 2025)
As the core theme of Early Modern Ottoman poetry, love inspired a plethora of Turkish research, the most enlightening of which explored questions of terminology, semantics, and mystic dimensions. Internationally, however, there have been few publications on this subject. This book scrutinizes the different strands of ʿışḳ, passionate love, their various backgrounds, and studies specific poets who engaged with this multifaceted concept.